Pelatihan Tahapan Arsip Digital Untuk Keamanan Data Bagi Para Siswa Di SMK PRAYATNA - 2 MEDAN - Hendarti, Ricca; Candra, Candra; Tambunan, Hotbona Novandi; Aulia, Muhammad Rizki; Tanjung, Febrina Soraya (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
The Students of SMK Swasta Prayatna Medan have not used Digital Archives technology because they only use the internet for entertainment or information sharing and are not focused on Digital Archives. So, students of SMK Swasta Prayatna 2 Medan need instruction and guidance on how to manage digital archives. The purpose of this Community Service activity is to provide students with knowledge about the importance of managing and using Digital Archives and also to assist students in setting up a system and knowing the right way to manage and use Digital Archives. This training involves a series of systematic stages starting from an explanation of the implementation of management in the era of the industrial revolution 4.0, an introduction to manual archive management systems, digital archives and an introduction to software for implementing digital archives namely Microsoft Access and Google Drive. After the training, participants gave good feedback and felt very helpful in understanding the implementation of digital-based archive management at SMK Prayatna 2 Medan.